Project benefit realisation and project management : the 6Q governance approach - Young, Raymond C., 1961-; Zerjav, Vedran (John Wiley & Sons, Inc., 2022)
"The main feature of this book will be to illustrate that there is a difference between project management success and project success. Although the traditional approach to project management has focused on considerations of time, budget and quality, this book will focus on project success understood in terms of the realisation of project benefits. Research has shown that projects very rarely succeed to realise benefits without top management support so this handbook emphasises and presents projects in the context of the needs of the top manager. It will deliver specific guidance for top managers and other stakeholders involved with projects across areas of construction, technology development, and business transformation, as well as those who find themselves in the role of the accidental project manager--those appointed to projects but with little project experience, who need to learn how to manage projects in the shortest time possible. It is concise without oversimplifying issues and does not fall into the trap of a "one-size-fits-all' approach. It provides a number of carefully selected examples to show how concepts can be applied to different types of projects, including those in engineering and construction, information and telecommunication, and organisational change"-- Resumé vydavatel .
Keywords: projektový management; project management; elektronické knihy; kolektivní monografie; electronic books; collective monographs